Irreversible vision loss in antiphospholipid syndrome complicated by pre-eclampsia: a case presentation and literature review - Sara Mirzaeian; Saeed Zarrabi; Mahdieh Mottaghi (BMC Pregnancy and Childbirth)
Abstract Background Previous literature has reported cases of reversible visual loss associated with pre-eclampsia. Here, we present a patient with severe pre-eclampsia and a history of antiphospholipid syndrome (APS) who experienced irreversible visual loss. Case presentation An 18-year-old woman, gravida 2, abortion 1, with a history of antiphospholipid syndrome, was diagnosed with severe pre-eclampsia at 34 weeks of gestation. The patient had highly triple positive antiphospholipid antibodies and was on aspirin and enoxaparin 40 mg daily throughout her pregnancy. Despite timely cesarean section and control of blood pressure, the patient developed bilateral visual loss due to serous retinal detachment and acute angle-closure glaucoma. Although the patient received ophthalmologic interventions, anticoagulant, and immunosuppressive therapy, her vision failed to recover, and at five years of follow-up, the patient remained legally blind. Conclusion Our case highlights the importance of monitoring pregnant women with APS who, despite receiving aspirin and LMWH treatments throughout pregnancy, still present with pre-eclampsia. This underscores the need for proper prophylaxis and timely interventions to prevent catastrophic outcomes.